If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5r(4r + 3) = 0 Reorder the terms: 5r(3 + 4r) = 0 (3 * 5r + 4r * 5r) = 0 (15r + 20r2) = 0 Solving 15r + 20r2 = 0 Solving for variable 'r'. Factor out the Greatest Common Factor (GCF), '5r'. 5r(3 + 4r) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'r' equal to zero and attempt to solve: Simplifying r = 0 Solving r = 0 Move all terms containing r to the left, all other terms to the right. Simplifying r = 0Subproblem 2
Set the factor '(3 + 4r)' equal to zero and attempt to solve: Simplifying 3 + 4r = 0 Solving 3 + 4r = 0 Move all terms containing r to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4r = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 4r = 0 + -3 4r = 0 + -3 Combine like terms: 0 + -3 = -3 4r = -3 Divide each side by '4'. r = -0.75 Simplifying r = -0.75Solution
r = {0, -0.75}
| -0.4=-12 | | X^3+2x^2+9x=0 | | 9x+4x=22-6x | | D=4*16 | | sinA=0.27 | | (2a+b+3c)2+(3a+2b-c)2= | | -7a(4a-4)= | | X^3+2x^2+3x+6x=0 | | x^2-(3x)-15=3 | | (3n+1)(n-5)=0 | | 49+b^2=41 | | 24=3(a-1)-3(2a+2) | | 4/5z=1-1/5z | | D=4t^2 | | 18x-32=7x+16 | | D=4(16)t^2 | | x^2-5=x+1 | | 9y-14-5y+9=0 | | 7h+14=9n+36-24 | | 3n+4=0 | | 29*11= | | 0.5x=7+12x | | 26+n=48 | | 2x(16x^2-40x+25)-8x^2*(5-4x)=0 | | =-x+4x-2 | | -12x+-18=44 | | -2=-2.5(4)+b | | 2g-20+8g=1-g | | (10^(-1/2))*(10^(5/2)) | | 5x^8=15x^6 | | -2k+2m=m | | 81-(8*11)= |